Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China - Qian, Yu-Han; Du, Yu-Zhou (Zootaxa, 2017)
Two new species of the genus Rhopalopsole, R. brevidigitata Qian & Du, sp. nov. and R. faciursina Qian & Du, sp. nov. are described and illustrated from Yunnan Province of southwestern China. The new species are compared to similar taxa in the R. vietnamica and R. shaanxiensis groups, respectively.